1847-48 Va. Acts 67, ch. 79, § 1 - (:unkn) unknown (My University, 1846)
That if any person shall unlawfully shoot at another in any public square ... with intent in so doing to maim, disfigure, disable or kill such person, or to do him some other bodily harm, ... every such offender, his aiders and abettors, shall be guilty of a high misdemeanor. and shall on conviction, be punished by imprisonment in the common jail for a period not less than six months nor more than three years...
Keywords: COMMITTING CRIME W/ WEAPON; DISCHARGE; DUELING